The Analysis of Industry-Specific Auditor Concentration: Towards an Explanatory Model. - Eichenseher, John W.; Danos, Paul (The Accounting Review, 1981)
ABSTRACT: This study is both a replication and an extension of prior work on auditor concentration in specific industries. By expanding the client population sevenfold, more comprehensive measurement of concentration is obtained than was possible in previous research. Prior studies' conclusions concerning the variability of auditor concentration across industries are supported, but the levels of concentration appear to be lower when a surrogate for audit fees is employed as the measure of CPA-firm activity levels. An important finding is that concentration measures are quite sensitive to the CPA-firm activity measure employed. A model is posited for explaining the level of auditor concentration in any given industry. The model states that auditor concentration is a positive function of the degree of client-industry regulation and capital market activity. Tests of this model across 54 industries indicate statistically significant positive associations between the two proposed explanatory variables, and the level of CPA-firm concentration.